Selective Extraction of ω-3 Fatty Acids from Nannochloropsis sp. Using Supercritical CO(2) Extraction - Leone, Gian Paolo (Molecules, 2019)
In this article, microalgae Nannochloropsis sp. was used for fatty acid (FA) extraction, using a supercritical fluid-carbon dioxide (SF-CO(2)) extraction method. This study investigated the influence of different pre-treatment conditions by varying the grinding speed (200–600 rpm), pre-treatment time (2.5–10 min), and mixing ratio of diatomaceous earth (DE) and Nannochloropsis sp. biomass (0.5–2.0 DE/biomass) on FAs extraction. In addition, the effect of different operating conditions, such as pressure (100–550 bar), temperature (50–75 °C), and CO(2) flow rate (7.24 and 14.48 g/min) on eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) recovery, was analyzed. Experimental data evidenced that, keeping constant the extraction conditions, the pre-treatment step enhanced the FAs extraction yield up to 3.4 fold, thereby the maximum extracted amount of FAs (61.19 mg/g) was attained with the pre-treatment with a ratio of DE/biomass of 1 at 600 rpm for 5 min. Moreover, by increasing both SF-CO(2) pressure and temperature, the selectivity towards EPA was enhanced, while intermediate pressure and lower pressure promoted DHA recovery. The highest amount of extracted EPA, i.e., 5.69 mg/g, corresponding to 15.59%, was obtained at 75 °C and 550 bar with a CO(2) flow rate of 14.48 g/min, while the maximum amount of extracted DHA, i.e., ~0.12 mg/g, equal to 79.63%, was registered at 50 °C and 400 bar with a CO(2) flow rate of 14.48 g/min. Moreover, the increased CO(2) flow rate from 7.24 to 14.48 g/min enhanced both EPA and DHA recovery.